Empowering leadership during the COVID-19 outbreak: Implications for work satisfaction and effectiveness in organizational teams - Cremers, Erik Eduard; Curşeu, Petru Lucian (Frontiers in Psychology, 2023)
The COVID-19 pandemic generated unprecedented challenges for the social and organizational life. We set out to explore how empowering leadership and leadership support was affected as a team-based organization started to implement flexible and remote work practices after the outbreak of COVID-19 pandemic. We use data on work satisfaction and effectiveness collected just before and immediately after the COVID-19 outbreak in 34 organizational teams in this large organization. Our results show that the COVID-19 outbreak did not significantly impact perceptions of empowering leadership nor perceived leadership support. However teams that experienced changes in empowering leadership also reported proportional changes in work satisfaction and effectiveness. Finally we show that the association between empowering leadership and work satisfaction in teams is moderated by team size, such that the strength of the association is higher in small rather than large organizational teams. We conclude by arguing that the team-based organization absorbed well the impact and disruptions associated with the COVID-19 outbreak and we point towards the role of empowering leadership for the work satisfaction and effectiveness in organizational teams with team size as a factor regarding the division and diffusion of impact of empowering leadership on work satisfaction in teams.